Strategi Pembelajaran Mendalam Kontekstual Model ASYIK, ATIK, dan SIUUL dalam Pendidikan Anak Usia Dini Inklusif di Era Disrupsi - Sri Watini; Alawiyah Alawiyah; Andriyanti Andriyanti; Maturrohmah, Bibin Siti; Ekawati Andayani; Mira Humayrah; Yazid Yazid (FKIP, Universitas Palangka Raya, 2026)
Inclusive Early Childhood Education (PAUD) faces significant challenges in the era of digital disruption, particularly in integrating technology with meaningful and contextual learning. This study aims to develop and implement a contextual deep learning strategy through the ASYIK, ATIK, and SIUUL models. The research used a participatory workshop method combined with experiential learning and collaborative inquiry approaches, involving 50 PAUD practitioners in the Cikarang area. The findings showed a significant increase in participants' knowledge and a very high level of satisfaction, with 98% reporting satisfaction or high satisfaction. The learning simulations demonstrated the successful application of creative and contextual strategies to support inclusive education for children with special needs. Participants were highly motivated to implement these models in their institutions. The study recommends continuous technical support, the development of adaptive learning media, and the establishment of practitioner communities to ensure the sustainable implementation of inclusive education. These efforts are essential to enhance the quality and inclusiveness of early childhood education in the digital era.